IMPLEMENTASI NILAI-NILAI PENDIDIKAN MODERASI BERAGAMA MELALUI PERAN FORUM KERUKUNAN UMAT BERAGAMA (FKUB) KABUPATEN GRESIK - Dinda Mulidatul Hasanah; Muhammad Shohib (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The phenomenon that often occurs in Indonesia is tolerant, radical and liberal attitudes. Friction often occurs between religious communities. If there is no follow-up action from the government, it is feared that divisions and clashes will occur between religious communities. Therefore, one way to anticipate this problem is the need for an association that has a special task in maintaining harmony between religious communities by instilling the values ​​of religious moderation. As has been stipulated by the government in Joint Ministerial Regulations Number 9 and 8 regarding the formation of FKUB as a mediator between religious communities to prevent divisions. Departing from the above reality, it can be of particular interest for researchers to analyze the implementation of religious moderation education values ​​through the role of the Gresik Regency FKUB. The approach in this research uses a qualitative research approach. The type of research is field research. Data collection uses interviews, observation and documentation.To implement the values ​​of religious moderation education there are several efforts in collaboration with the Gresik Regency Ministry of Religion such as, the Religious Moderation Village, the coronation of the Harmony Awareness Village. and make working visits to other FKUBs. The supporting and hindering factors in carrying out the duties of the Gresik Regency FKUB are related to internal and external factors.